PERLINDUNGAN TENAGA KERJA INDONESIA DI QATAR: TINJAUAN PERAN PEMERINTAH DALAM MELINDUNGI TKI DI QATAR - Aprilia Restuning Tunggal (Dauliyah Journal of Islamic and International Affairs, 2017)
The Indonesian government’s policy of protecting Indonesian workers in Qatar is a mandate from the member countries of the Republic of Indonesia; Therefore, the Indonesian government should be able to carry out this mandate well and be responsible. International law states that a country has the right and responsibility to protect its citizens abroad. Furthermore, the regulation on the protection of foreign citizens is also regulated in the 1961 Vienna Convention on article 3 on diplomatic relations between countries. The protection of the state against citizens abroad is known as Diplomatic Protection. Currently, the number of Indonesian workers in Qatar is 43,000, so the government needs to protect, and serve the citizens. The Government of Indonesia has established its citizenship service system at the Embassy of the Republic of Indonesia to Doha Qatar, and provides legal assistance to Indonesian citizens and workers living in Qatar. So far the government’s policy to protect Indonesian workers in Qatar has been running maximally and in accordance with the legal corridor.